1976
DOI: 10.1007/bf00033486
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in the vertical distribution and buoyancy of Microcystis aeruginosa Kütz. emend. Elenkin in Rostherne Mere, England

Abstract: Distribution and buoyancy studies in Rostherne Mere (depth : 30m) show that the life-cycle of Microcystis is intimately related to the cycle of thermal stratification : colonies overwinter on the bottom muds, but migrate to the epilimnion in summer, returning again in late autumn or winter .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0
2

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 9 publications
5
52
0
2
Order By: Relevance
“…It is likely that these algae, though physiologically inactive, had lost their buoyancy. Autumnal reductions in buoyancy, possibly as a result of enzymatic weakening of the gas-vacuole membranes (Walsby, 1971), have been observed in previous years in this and other meres (Reynolds, 1973b;Reynolds & Rogers, 1976). …”
Section: _(a )supporting
confidence: 54%
“…It is likely that these algae, though physiologically inactive, had lost their buoyancy. Autumnal reductions in buoyancy, possibly as a result of enzymatic weakening of the gas-vacuole membranes (Walsby, 1971), have been observed in previous years in this and other meres (Reynolds, 1973b;Reynolds & Rogers, 1976). …”
Section: _(a )supporting
confidence: 54%
“…The areal equivalent of the vernal diatom maxima (units cm-3) are calculated from equation (1), thus: P = C x 13.7 × 100 (1) where C is the concentration of algal units ml-1 of integrated 4.5 m column samples. During summer, the isothermal depth can never exceed that of the epilimnion, typically less than 8 m (Grimshaw & Hudson, 1970;Reynolds & Rogers, 1976). The areal equivalents of algal concentrations are approximated from equation (2): P=Cx 8.0 × 100 (2) With the exception of those for Nitzschia, the areal catches of the diatom species are apparently overestimated by factors of 2-20 for the commoner forms, and increasing to 330 in the case of Melosira varians.…”
Section: Quantitative Assessment Of Trap Performancementioning
confidence: 99%
“…Sedimentation of Microcystis populations is associated with declining water temperature (see data of Renolds & Rogers, 1976;Rother & Fay, 1977;Takamura et al, 1984), but temperature changes have not previously been shown to cause loss of buoyancy. In this paper direct evidence is presented for light-mediated regulation of buoyancy in a natural population of Microcystis and for the involvement of low temperature in the seasonal loss of buoyancy.…”
mentioning
confidence: 99%